The Directions of and Research Methods in Behavioural Accounting and Neuroaccounting - Gos, Waldemar (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2020)
Objective: The study provides an overview of directions in research and selected methods which can be used in neuroaccounting, a branch of behavioural accountancy. Research Design & Methods: The study employs content analysis and deductive and inductive reasoning. Findings: This overview introduces the author’s research on the subject of biological determinants of neuroaccounting. Implications / Recommendations: Behavioural economics is a newer fields of economics, explaining phenomena through the prisms of sociology and psychology. Neuroeconomics, on the other hand, uses research methods typically applied in biology, chemistry and medicine to describe processes that take place in the human brain. Ongoing changes in economics also affect accounting. Contribution: The article examines the notion that behavioural accounting and neuroaccounting are interdisciplinary fields of knowledge where various research methods can be used.